On discovery, restricting lawyers, and the settlement rate - Florian Baumann; Tim Friehe (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This paper analyzes the principal-agent relationship between a plaintiff and his or her lawyer when the lawyer's investment in discovery is private information. The plaintiff uses the level of the contingency fee and potentially also restrictions on settlements to guide the lawyer's decision-making. We show that the plaintiff can increase the lawyer's investment in discovery by disallowing a settlement in the event of unsuccessful discovery, thereby reducing the pair's joint surplus. We establish that such a restriction may indeed be privately optimal for the plaintiff but can cast doubt on the social desirability of the discovery process.
Keywords: K41; H23; 330; litigation; discovery; moral hazard; principal-agent relationship